Metaphor as a window on talk about trauma and post traumatic growth - Costa, Adriana; Steen, Gerard (Scripta, 2014)
People who have suffered traumatic experiences struggle to speak out loud about those events and the resulting pain. At the same time, talking about the trauma and its consequences is a precondition for recovery. This paper adopts Conceptual Metaphor Theory (LAKOFF; JOHNSON, 1980) to investigate how and when trauma sufferers use metaphor as a helpful means to talk and reason about their life stories. It analyzes a set of 7 interviews with traumatized people to study Posttraumatic Growth (PTG), a positive change in people who have struggled with challenging situations in life. The verbal data were analyzed with a cognitive-linguistic approach to metaphor, focusing on a selection of central metaphors for emotions of trauma and life. The patterns that emerged from this analysis were used to construct a model that reveals how survivors use the same conceptual metaphors in two different ways to talk about the different moments of the trauma itself and the subsequent process of recovery.